P37 Phase 1 evaluation of bintrafusp alfa (M7824), a bifunctional fusion protein targeting TGF-β and PD-L1, in cervical cancer. (1st November 2019) - Allan, S; Braiteh, F; Calvo Aller, E; Cervantes, A; Edenfield, W; Li, T; Rasschaert, M; Park-Simon, T-W; Longo, F; Paz-Ares, L; Spira, A; Strauss, J; et al.
Abstract : Introduction/Background: Globally, cervical cancer is one of the most common and lethal gynaecological cancers. Advanced/metastatic disease is typically treated with chemotherapy, often with poor objective response rates (ORRs) and durations of response (DORs) in pretreated patients; ORRs with anti-PD-1 therapies range from 12%-26%. Bintrafusp alfa* (M7824) is an innovative first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β 'trap') fused to a human IgG1 mAb blocking PD-L1. We report safety and efficacy in patients with cervical cancer treated with bintrafusp alfa in dose-escalation and expansion phases of an ongoing phase 1 trial (NCT02517398 ). Methodology: Patients with advanced/metastatic disease received bintrafusp alfa 0.3–30 mg/kg (dose-escalation, n=10) or 1200 mg (expansion, n=15) Q2W until PD, unacceptable toxicity, or withdrawal. Treatment past PD was allowed if adverse events (AEs) were tolerable and no new treatment was indicated. Primary endpoints were safety (dose-escalation) and BOR (expansion). Results: As of 9 January 2019, 25 patients were treated for a median duration of 9.6 (range, 2.0–72.0) weeks. Six patients had confirmed responses per RECIST 1.1 (ORR, 24.0%); 5/6 responses were ongoing at data cutoff (median DOR not reached; range, 2.3±24.9+ months). One additional patient had a delayed PR that was ongoing for 8.7 months at data cutoff, with 73.3% disease shrinkage after initial PD (total clinical response rate, 28.0%). Responses occurred irrespective of PD-L1 protein expression: 1 patient with PD-L1-negative disease had a response. Grade 3 treatment-related AEs (TRAEs) occurred in 6 patients (24.0%); 1 patient experienced a grade 4 TRAE (4.0%; hypokalaemia). Six patients discontinued treatment due to TRAEs. No treatment-related deaths occurred. Conclusion: Bintrafusp alfa has a manageable safety profile and promising clinical activity with durable responses. Further investigation of bintrafusp alfa in cervical and other HPV-associated cancers is ongoing (NCT03427411 ). Updated results will be presented. Disclosure: TL discloses honoraria from Foundation Medicine, Takeda, and PUMA, and receives grant/research support from Foundation Medicine, Pfizer, AstraZeneca, Hengrui, and Eureka. JS discloses inventorship on a National Institutes of Health patent related to the work. LSO and ID disclose employment with EMD Serono, Inc. CH discloses employment with Merck Healthcare KGaA. JLG discloses that National Cancer Institute has a cooperative research and development agreement with EMD Serono, Inc. and discloses inventorship on a National Institutes of Health patent related to the work. All remaining authors have nothing to disclose. Funding for this trial was provided in part by the Center for Cancer Research, National Cancer Institute, and National Institutes of Health Clinical Center. This trial was sponsored by Merck Healthcare KGaA, Darmstadt, Germany, and is part of an alliance between Merck Healthcare KGaA and GlaxoSmithKline. *Proposed INN